Residual Axillary Burden After Neoadjuvant Chemotherapy (NACT) in Early Breast Cancer in Patients with a priori Clinically Occult Nodal Metastases – a transSENTINA Analysis - Kolberg, Hans-Christian; Kühn, Thorsten; Krajewska, Maja; Bauerfeind, Ingo; Fehm, Tanja N.; Fleige, Barbara; Helms, Gisela; Lebeau, Annette; Stäbler, Annette; Schmatloch, Sabine; Hauschild, Maik; Schwentner, Lukas; Schrenk, Peter; Loibl, Sibylle; Untch, Michael; Kolberg-Liedtke, Cornelia (Geburtshilfe und Frauenheilkunde, 2020)
Background Among patients with breast cancer undergoing neoadjuvant chemotherapy (NACT), the association between pathological complete remission (pCR) in the breast and clinical/pathological parameters is well established, whereas the association between these parameters and residual axillary involvement after NACT remains unclear.Methods Patients with clinically occult nodal metastases (i.e. negative by clinical assessment but positive by SLNB prior to NACT, i.e. Arm B of the SENTINA trial) were included in the presented analysis. All patients received a second sentinel lymph node biopsy (SLNB) and axillary dissection after NACT. Univariate and multivariate analyses were carried out to evaluate the association between clinical/pathological parameters and axillary involvement after NACT.Results Arm B of the SENTINA study contained 360 patients, 318 of which were evaluable for this analysis. After NACT, 71/318 (22.3%) patients had involved SLNs or non-SLNs after NACT. Overall, 71/318 (22.3%) patients achieved a pCR in the breast. Associations of extranodal spread, lack of multifocality and pCR in the breast with residual axillary burden were statistically significant. In a descriptive analysis including all patients with clinically negative axilla before NACT in the SENTINA trial 1.2% of triple negative (TN) patients and 0.5% of HER/2 positive patients had residual axillary disease in case of a breast pCR.Conclusions Patients in the SENTINA trial with clinically negative axilla and involved SLNs still carried a significant risk of nodal metastases after NACT. However, the risk of residual axillary burden was particularly low in TN and HER/2 positive tumors in case of a breast pCR.
Keywords: prediction of lymph node status; primary systemic therapy; SENTINA trial; sentinel lymph node biopsy